2019
DOI: 10.1073/pnas.1907154116
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Sox2-dependent Merkel cell carcinoma to a differentiated neuron-like phenotype by T antigen inhibition

Abstract: Viral cancers show oncogene addiction to viral oncoproteins, which are required for survival and proliferation of the dedifferentiated cancer cell. Human Merkel cell carcinomas (MCCs) that harbor a clonally integrated Merkel cell polyomavirus (MCV) genome have low mutation burden and require viral T antigen expression for tumor growth. Here, we showed that MCV+ MCC cells cocultured with keratinocytes undergo neuron-like differentiation with neurite outgrowth, secretory vesicle accumulation, and the generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 67 publications
(94 reference statements)
3
62
0
Order By: Relevance
“…The discrepancy between induction of mRNA and lack of KRT8 protein in immunostaining upon GLI1 expression might be explained by protein levels below the detection limit of the antibody used. Nevertheless, together, these results suggest that GLI1, the executor of the sonic hedgehog pathway, is capable of initiating the first step of MC differentiation via SOX2 induction [6,9]. .…”
Section: Gli1 Expression In Keratinocytes Induces MC Lineage Markersmentioning
confidence: 86%
See 1 more Smart Citation
“…The discrepancy between induction of mRNA and lack of KRT8 protein in immunostaining upon GLI1 expression might be explained by protein levels below the detection limit of the antibody used. Nevertheless, together, these results suggest that GLI1, the executor of the sonic hedgehog pathway, is capable of initiating the first step of MC differentiation via SOX2 induction [6,9]. .…”
Section: Gli1 Expression In Keratinocytes Induces MC Lineage Markersmentioning
confidence: 86%
“…Subsequent studies revealed that approximately 80% of MCC cases are Merkel cell polyomavirus (MCPyV)-positive, and expression of the two viral T antigens (TA) (small T (sT) and large T antigens (LT)) are considered as the main drivers for carcinogenesis and growth of such tumors [2]. Interestingly, while several candidates, such as epithelial cells, fibroblasts, neuronal progenitors, or B cells, have been proposed, the nature of the cells giving rise to MCC following infection remains unknown [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…We also find that neural cells cluster with the MCC cell lines, albeit more distantly than the cell lines and types mentioned above. Interestingly, a recent study reported reversion of MCC tumor cells to neuron-like cells after T-Antigen knockdown, suggesting neural precursor cells as putative MCC origin [60].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Intriguingly, they found that LSD1 and RCOR2 binding sites overlap with those of ATOH1, a key transcription factor of normal Merkel cell development (Bardot et al , 2013; Park et al , 2020). Other studies found that the inhibition of the T antigens induces cell cycle arrest (Houben et al , 2010) and induces neuronal differentiation when co‐cultured with keratinocytes (Harold et al , 2019). Collectively, these data suggest that T antigen‐mediated transformation relies on LSD1 to suppress differentiation toward a post‐mitotic Merkel cell fate and lock MCC cells in a stem‐like state.…”
Section: Discussionmentioning
confidence: 99%